The Crude Oil Price Influence on the Brazilian Industrial Production - de Salles, Andre Assis; Almeida, Pedro Henrique Acioli (Scientific Research, 2017)
The oil price is a relevant variable for economic policy makers in countries where this commodity is the main energy source as well as in other countries where crude oil is not the only energy source. The sudden variations in the crude oil price cause direct influence in the national economies bringing changes in foreign trade, investments and productive activities. Therefore, the crude oil market is very important for the economic development. Furthermore, crude oil is directly or indirectly present in all productive activities. This way the crude oil market is related to the industrial production indicators. Many researches aim at establishing the stochastic process that can represent the movements of macroeconomic indicators through the oil price returns or variations that have been done in recent years. The purpose of this work is to study the relationship between crude oil prices and selected industrial production indicators of the Brazilian economy. To do that this work carried out cointegration and causality tests, from VAR estimations, and impulse response analysis. The data used in this study is monthly macroeconomic indicators, mentioned above, and the Brent crude oil type price negotiated in the London Market. All data used is in US$. The period of the sample used is from January 2002 to October 2015.
Keywords: Oil Price; Industrial Production; Cointegration; Causality; Impulse Response Function